Design of X-shaped double split tee joints accounting for moment–shear interaction. (January 2015) - Latour, M.; Rizzano, G.
Abstract: Dealing with steel moment resisting frames (MRFs), the latest version of Eurocode 8 allows us to dissipate the seismic input energy in connections provided that their characteristics under cyclic loads are certified by means of experimental testing. Within the beam-to-column joint typologies to be used in seismic resistant steel frames, the double split tee joint (DST) represents an interesting solution due to its easy fabrication and repair after a destructive seismic event. Nevertheless, the cyclic behavior of this joint typology is usually characterized by pinching and strength degradation phenomena due to the plastic engagement of the rectangular T-stubs which compromises the use of DST joints as dissipative elements. Within this framework, in this paper, in order to improve the hysteretic behavior of this connection typology, a new type of dissipative DST joint is presented. In particular, the proposed dissipative T-stub is designed substituting the rectangular T-stubs with the so-called X-shaped T-stubs, whose flange plates are cut into an hourglass shape similar to that of ADAS dampers. In particular, in the paper, a model that is able to predict the resistance of the proposed X-shaped T-stubs accounting for moment–shear interaction is developed and rules for designing the optimum shape of dissipative DST joints are proposed. Finally, the results of an experimental activity on real scale joints are presented aiming to verify the reliability of the proposed design approach and to compare the cyclic behavior of classical and X-shaped DST joints evidencing the benefits provided by the proposed dissipative joint. Highlights: An innovative dissipative double split tee joint with hourglass shaped flanges is proposed; A model able to predict the resistance of the proposed X-shaped T-stub accounting for the moment-shear interaction effects is presented; A criteria able to define an optimum shape accounting for the reduction of resistance due to shear is proposed; An experimental analysis on real scale joints devoted to validate the proposed design approach is presented; A significant improvement in terms of energy dissipation capacity and ductility is provided by the proposed joint